2022
DOI: 10.3390/diagnostics12092095
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Infectious Keratitis in Taiwan: An Update on Predisposing Factors, Microbiological and Antibiotic Susceptibility Patterns

Abstract: Infectious keratitis (IK) represents a major cause of corneal blindness. This study aims to investigate the demographics, risk factors, microbiological characteristics and antibiotic susceptibility patterns of IK in Taiwan over the past 15 years. A retrospective population-based study was conducted using the Chang Gung Research Database. Patients with IK were identified by diagnostic codes for corneal ulcer from 2004 to 2019. Of 7807 included subjects, 45.2% of patients had positive corneal cultures. The propo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…First, we found a low number of pathogens recovered from microbial scrapping (<50%) that might be due to previously given antimicrobial therapy, this was similar to a recent study in Taiwan, that only recovered 3990 pathogens from 7807 corneal scraping cultures (51.1%) therefore we could not differentiate the IL-6 changes between different causative pathogens. [ 17 ] Second, no data regarding predisposing risk factors on the treatment effect of lysate. Future studies who include the predisposing factors in the analysis will give a better understanding of the effect of lysate on the disease.…”
Section: Discussionmentioning
confidence: 99%
“…First, we found a low number of pathogens recovered from microbial scrapping (<50%) that might be due to previously given antimicrobial therapy, this was similar to a recent study in Taiwan, that only recovered 3990 pathogens from 7807 corneal scraping cultures (51.1%) therefore we could not differentiate the IL-6 changes between different causative pathogens. [ 17 ] Second, no data regarding predisposing risk factors on the treatment effect of lysate. Future studies who include the predisposing factors in the analysis will give a better understanding of the effect of lysate on the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A male predominance was found in our study with 74.7% males and 25.3% females. Similar to our study Wang JJ., et al [7],…”
Section: Treatment and Its Outcomesmentioning
confidence: 96%
“…For Gram-positives, five studies found 0%-29% resistance to cephalosporins [84][85][86][87][88] ; four studies reported 0%-52% resistance to aminoglycosides 84,[86][87][88] ; and six studies 0%-47% resistance to fluoroquinolones. [84][85][86][87][88][89] For Gram-negatives, five studies found 0%-50% resistance to cephalosporins 88 ; and seven studies 0%-48% resistance to aminoglycosides and 3%-57% to fluoroquinolones. [84][85][86][87][88][89][90] In summary, for Gram-positives, the range of resistance to cephalosporins was similar in Australia, North America, and Asia between 0% and 35%.…”
Section: Keratitismentioning
confidence: 99%
“…[84][85][86][87][88][89] For Gram-negatives, five studies found 0%-50% resistance to cephalosporins 88 ; and seven studies 0%-48% resistance to aminoglycosides and 3%-57% to fluoroquinolones. [84][85][86][87][88][89][90] In summary, for Gram-positives, the range of resistance to cephalosporins was similar in Australia, North America, and Asia between 0% and 35%. Similarly to the range of resistance to fluoroquinolones (5%-27%) in the UK, Australia, and North America.…”
Section: Keratitismentioning
confidence: 99%
See 1 more Smart Citation